Indonesian Muslims’ Discourse of Husband-Wife Relationship - Nina Nurmila (Al-Jami'ah Research Centre, 2013)
Islam as the majority religion in Indonesia has important influence on its adherents, including in the matter of husband-wife relationship. This paper aims at discussing Indonesian Muslims’ discourse of husband-wife relationship. In Indonesia, Muslim women are mainly accustomed to stay at home, to respect and to obey their husbands. This construction of women’s domestication and subordination is usually based on the two most frequently quoted hadiths: (1) on the curse of angel for women who refuse to have sex with their husband; and (2) on the woman whose parent enters paradise because of the woman’s obedience to her husband. The two traditions are commonly used to justify this construction of husband-wife relationship. However, since the coming influence of global Muslim feminism in Indonesia in the early 1990s, this traditional construction of husband-wife relationship has been criticized by the emerging Indonesian Muslim feminist scholars whose works have provided new perspective on the discourse of husband-wife relationship. Different from the mainstream perspective which tends to domesticate and subordinate women, the new perspective gives position to women and should be treated as equal partner of their husband.[Islam sebagai agama mayoritas di Indonesia berpengaruh besar dalam keseluruhan aspek kehidupan pemeluknya, tidak terkecuali dalam aspek hubungan suami-istri. Artikel ini mendiskusikan diskursus relasi suami-istri yang dilontarkan oleh pemikir Islam di Indonesia. Di Indonesia, perempuan Muslim kerap ditempatkan dalam ranah domestik saja, dituntut untuk menghormati dan mematuhi suami mereka. Cara pandang domestifikasi dan subordinasi perempuan tersebut biasanya didasarkan pada hadis mengenai murka para malaikat kepada perempuan yang menolak ajakan berhubungan badan para suami dan hadis yang menceritakan kisah orang tua seorang istri yang tunduk terhadap perintah suaminya. Namun, sejak dekade 1990an, ketika feminisme global diperkenalkan, konstruksi tersebut dikritik oleh sebagian kalangan akademisi feminist Muslim, yang karya-karyanya mengetengahkan perspektif baru mengenai diskursus hubungan suami-istri. Berbeda dengan perspektif mainstream, perspektif baru ini menempatkan perempuan pada posisi yang sejajar dengan suami mereka.]